DAMPAK PEMILIHAN UMUM SERENTAK BAGI PEMBANGUNAN DEMOKRASI INDONESIA - Prasetyoningsih, Nanik (Jurnal Media Hukum, 2014)
Elections are a democratic mechanism to elect person who will represent the people and lead the government. Since 1955; Indonesia has been held 11 general elections. According to the Article 1 (3) 1945 Constitution, which mentioned the principle of popular sovereignty; it means that people hold the highest authority should be given the opportunity to determine the power. The aim of this study was to analysis of the effect of electoral systems for developing Indonesia’s democracy. Talking on democratic government its always related with the degree of legitimation, means that the government should have the legitimation from the people trough the general election. The type of research is a legal research with normative point of view. The approach of the research are statue and conceptual approach. The main data of this research is a secondary data, which consist of a primary legal material and secondary legal material. In 2014, Indonesia hosted the general election to elect the parliament members and President which held in the different day. A month before general election done, the Constitutional Court announced the judicial review verdict of Law Number 42 Year 2008. Constitutional Court decided the legislative elections and the election of the president and vice president were held simultaneously. Decision of constitutional court Number 14/PUUXI/2013 has legal implication on general election of 2014 and also general election of 2019. From the very beginning the new law was endorsed, the General Election Commission have made all preparations to organize simultaneous elections in Indonesia. The goal is mainly to reduce costs. Indonesian democracy has long been perceived as being too costly. The quality of democracy depends on the fairness of general election not the cost. Everybody get their rights properly and savely. This is important to ensure justice while at the same time avoiding possible conflict.